Ngawan: Representasi Mata Pencarian Masyarakat Pesisir Desa Seraya dalam Strategi Pemajuan Kebudayaan - Sitepu, Samuel Raskita; Wedasantara, Ida Bagus Oka (IAIN Madura, 2023)
One of the traditions that has become the livelihood of the coastal community in Seraya Village is ngawan. However, along with the influence of globalization, ngawan activities began to be abandoned., this is in line with public perceptions regarding the work of fishermen who are considered poor. The effort to preserve ngawan can be done by referring to the strategy of cultural promotion. This research was conducted with the following objectives: (1) to describe the life of coastal communities in Seraya Village, and (2) to understand the strategy of cultural promotion in various aspects of the life of coastal communities in Seraya Village. The method used in this research is qualitative with techniques such as participant observation, in-depth interviews, and literature studies to produce a holistic ethnographic work. The subject selection used a purposive model, namely those who live in the coastal area of Seraya Village. The results showed that most of the coastal communities of Seraya Village have implemented cultural promotion strategies without realizing it, although the active role of the government to improve the welfare of coastal communities is still needed.